2016
DOI: 10.1021/acs.energyfuels.6b01568
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Catalytic Activity of Thermosensitive Ga2O3 Nanorods

Abstract: Gallium oxide (β-Ga 2 O 3 ) nanorods were prepared by ultrasonic irradiation of molten gallium in warm water to form α-GaO(OH). This precursor was then subjected to calcination in air at 600 °C for 3 h to form β-Ga 2 O 3 , as confirmed by Xray diffraction (XRD). Field emission scanning electron microscopy (FE-SEM)/high-resolution transmission electron microscopy (HRTEM) micrographs revealed the formation of well-organized nanotubes/nanorods with homogeneous size distribution. The average length of the β-Ga 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The catalytic activity of β-Ga 2 O 3 nanorods was examined during the dehydration reaction of xylose to furfural, and results showed that β-Ga 2 O 3 exhibits good activity and selectivity. The 94% yield of furfural is obtained at 150 • C within 12 h (Kumar et al, 2016). The inherent characteristics of the stimuli and thermoresponsiveness for gallium-based oxide nanoparticles catalyst might be key factors leading to higher production of furfural from xylose.…”
Section: Nanosized Metal Oxidesmentioning
confidence: 99%
“…The catalytic activity of β-Ga 2 O 3 nanorods was examined during the dehydration reaction of xylose to furfural, and results showed that β-Ga 2 O 3 exhibits good activity and selectivity. The 94% yield of furfural is obtained at 150 • C within 12 h (Kumar et al, 2016). The inherent characteristics of the stimuli and thermoresponsiveness for gallium-based oxide nanoparticles catalyst might be key factors leading to higher production of furfural from xylose.…”
Section: Nanosized Metal Oxidesmentioning
confidence: 99%
“…For instance, the optoelectronics community is currently addressing the need to produce single crystal Ga 2 O 3 with specific characteristics (i.e., p-type doping and improved thermal conductivity) that are essential for fabricating devices for power electronics . However, advances in the synthesis of nanostructured Ga-based oxide materials has expanded their utility. , Currently, there is an emphasis on understanding their properties in the context of catalysis, sensors, and biomedical modalities, such as targeted drug delivery, chemo/thermal/photodynamic therapy, and in vivo imaging. Properties of particular interest include unique conductivity and photoluminescence .…”
Section: Introductionmentioning
confidence: 99%
“…1 However, advances in the synthesis of nanostructured Ga-based oxide materials has expanded their utility. 2,3 Currently, there is an emphasis on understanding their properties in the context of catalysis, 4 sensors, 5 and biomedical modalities, 6 such as targeted drug delivery, chemo/thermal/photodynamic therapy, and in vivo imaging. Properties of particular interest include unique conductivity 7 and photoluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Such a surface oxide layer is formed either unintentionally, through prolonged exposure to air or water, or intentionally as a relatively thick layer of crystalline oxide formed by thermal oxidation of the surface. [28] Gallium oxide is a transparent oxide with a wide energy band gap of 4.8 eV [29] which, owing to its material properties, is a promising semiconductor material for a wide range of applications from semiconducting lasers, UV detectors, and high temperature gas sensors, to water splitting, [30,31] catalysis, [32,33] and hydrogen detectors. [34][35][36][37] The electronic transport properties of III-N semiconductors have been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%